An EZH2‐dependent transcriptional complex promotes aberrant epithelial remodelling after injury. (5th July 2021) - Le, Huy Q; Hill, Matthew A; Kollak, Ines; Keck, Martina; Schroeder, Victoria; Wirth, Johannes; Skronska‐Wasek, Wioletta; Schruf, Eva; Strobel, Benjamin; Stahl, Heiko; Herrmann, Franziska E; Campos, Alexandre R; et al.
Abstract: Unveiling the molecular mechanisms of tissue remodelling following injury is imperative to elucidate its regenerative capacity and aberrant repair in disease. Using different omics approaches, we identified enhancer of zester homolog 2 (EZH2) as a key regulator of fibrosis in injured lung epithelium. Epithelial injury drives an enrichment of nuclear transforming growth factor‐β‐activated kinase 1 (TAK1) that mediates EZH2 phosphorylation to facilitate its liberation from polycomb repressive complex 2 (PRC2). This process results in the establishment of a transcriptional complex of EZH2, RNA‐polymerase II (POL2) and nuclear actin, which orchestrates aberrant epithelial repair programmes. The liberation of EZH2 from PRC2 is accompanied by an EZH2‐EZH1 switch to preserve H3K27me3 deposition at non‐target genes. Loss of epithelial TAK1, EZH2 or blocking nuclear actin influx attenuates the fibrotic cascade and restores respiratory homeostasis. Accordingly, EZH2 inhibition significantly improves outcomes in a pulmonary fibrosis mouse model. Our results reveal an important non‐canonical function of EZH2, paving the way for new therapeutic interventions in fibrotic lung diseases. SYNOPSIS: TAK1‐mediated phosphorylation of EZH2 regulates fibrotic epithelial remodelling after injury. EZH2 inhibition improves outcomes in a pulmonary fibrosis model, suggesting that targeting the TAK1‐EZH2 axis has therapeutic efficacy for idiopathic pulmonary fibrosis (IPF). Chronic TGFβ1 treatment induces nuclear translocation of TAK1. EZH2 is liberated from PRC2 by TAK1‐mediated phosphorylation of threonine 311 (T311). EZH2 liberation is accompanied by an EZH1 switch to maintain H3K27me3 deposition at non‐target genes. Liberated EZH2 forms a transcriptional complex with nuclear actin and RNA Pol‐II to fine‐tune profibrotic gene expression. Abstract : TAK1‐mediated phosphorylation of EZH2 regulates fibrotic epithelial remodelling after injury. EZH2 inhibition improves outcomes in a pulmonary fibrosis model, suggesting that targeting the TAK1‐EZH2 axis has therapeutic efficacy for idiopathic pulmonary fibrosis (IPF).